2006
DOI: 10.5488/cmp.9.4.695
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence effect of viscosity on ultrathin lubricant film melting

Abstract: We study the melting of an ultrathin lubricant film under friction between atomically flat surfaces at temperature dependencies of viscosity described by Vogel-Fulcher relationship and by power expression, which are observed experimentally. It is shown that the critical temperature exists in both cases the exceeding of which leads to the melting of lubricant and, as a result, the sliding mode of friction sets in. The values of characteristic parameters of lubricant are defined, which are needed for friction re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…[10] the conditions under which the stick-slip friction regime corresponds to the intermittency mode inherent in self-organized criticality phenomenon are found. Effect of different types of temperature dependence of viscosity on the melting temperature of lubricant is taken into account [11].…”
Section: Introductionmentioning
confidence: 99%
“…[10] the conditions under which the stick-slip friction regime corresponds to the intermittency mode inherent in self-organized criticality phenomenon are found. Effect of different types of temperature dependence of viscosity on the melting temperature of lubricant is taken into account [11].…”
Section: Introductionmentioning
confidence: 99%
“…Let us write down the system of equations for the shear components of the stresses σ and the strain ε, as well as for the temperature T, using the units [7,[10][11][12][13][14][15]17] (1) for the variables σ, ε, and T, respectively, where ρ is the lubricant density; c v is the lubricant specific heat; T c is the critical temperature; η 0 ≡ η at T = 2T c is the char acteristic value of the shear viscosity η; τ T ≡ ρl 2 c v /κ is the thermal conductivity time; l is the lubricating layer thickness; κ is the thermal conductivity of the lubri cant; τ ε is the relaxation time of strain; and G 0 ≡ η 0 /τ ε is the characteristic value of the shear modulus:…”
Section: Stick Slip Modementioning
confidence: 99%
“…In our previous papers [7,[10][11][12][13][14][15]17], we have shown that the zero stationary stresses σ 0 correspond to the solidlike structure of the lubricant, while at σ 0 ≠ 0 the latter melts and transits to a liquidlike state, which corresponds to the plastic flow portion of the loading diagram. Transitions between the liquidlike and solid like structures are represented as phase transitions, but between different kinetic friction modes rather than between equilibrium thermodynamic phases; several kinetic friction modes may exist [1].…”
Section: Stick Slip Modementioning
confidence: 99%
See 2 more Smart Citations